2020
DOI: 10.1093/infdis/jiaa131
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Responses in Serum and Cerebrospinal Fluid From Neonates and Infants Infected With Parechovirus-A3 or Enteroviruses

Abstract: Background Parechovirus (PeV)-A3 and enteroviruses (EV) are the most common viruses causing sepsis and meningoencephalitis in neonates and young infants. Clinical manifestations of PeV-A3 infection are more severe than those of EV infection, and no pleocytosis with a positive polymerase chain reaction (PCR) result for PeV-A3 in cerebrospinal fluid (CSF) are characteristic findings. We hypothesized that innate immune responses to PeV-A3 and EV are distinct in serum and CSF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…PeV-A3 has emerged as a neuroinvasive virus. Clinical evidences revealed that PeV-A3 induced innate immune responses of cytokine/chemokine expression in neonates and infants (62) In addition to the PeV-A3 infection animal model in this study, other picornavirus infection animal models were previously established in mice to address critical issues. For example, the pathogenic mechanism of echovirus was revealed in the transgenic mice with human integrin very late antigen 2 (VLA-2, echovirus entry receptor) expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PeV-A3 has emerged as a neuroinvasive virus. Clinical evidences revealed that PeV-A3 induced innate immune responses of cytokine/chemokine expression in neonates and infants (62) In addition to the PeV-A3 infection animal model in this study, other picornavirus infection animal models were previously established in mice to address critical issues. For example, the pathogenic mechanism of echovirus was revealed in the transgenic mice with human integrin very late antigen 2 (VLA-2, echovirus entry receptor) expression.…”
Section: Discussionmentioning
confidence: 99%
“…PeV-A3 has emerged as a neuroinvasive virus. Clinical evidences revealed that PeV-A3 induced innate immune responses of cytokine/chemokine expression in neonates and infants ( 62 ). However, there was no suitable animal model for understanding neonatal PeV-A3 ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, prior studies lend credence to our data. A recent study by Habukha et al from Japan investigated expression of 22 cytokines and chemokines in the CSF and plasma of infants infected with EV and PeV-A3 [ 19 ]. Sixteen biomarkers overlapped between their study panel (n = 22) and ours (n = 21).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical characteristics and laboratory findings and their differences in EV- and PeV-A3-infected infants have been documented reasonably well. However, the data for host innate immune responses to EV and PeV-A3 infections in relation to the severity of clinical aspects and abnormalities in laboratory test results are still limited [ 13 , 14 , 19 ]. Therefore, the objective of our study was to evaluate cytokine and chemokine responses in the CSF and plasma of EV- vs PeV-A3-infected patients vs control subjects with neither EV nor PeV-A3, evaluating for possible differences in innate response between PeV-A3, EV, and controls.…”
mentioning
confidence: 99%
“…Imaging and histopathologic findings have prompted the hypothesis that hPeV associated CNS pathology may represent a virally driven vasculitic process. 50,51 Protein levels and cytology of CSF in hPeV positive patients were similar to that of uninfected CSF, 52 and CSF cytokine profiles were dominated by Th2-skewed cytokines. 53 By contrast, EV positive CSF contained Th1-cytokines including IL1β, IL6 and IL17.…”
Section: Discussionmentioning
confidence: 79%